2018
DOI: 10.5530/pj.2018.6.189
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characteristics and In vitro Antidiabetic and Antioxidant Activities of Premna serratifolia L. Leaf Infusion and Decoction

Abstract: Introduction: Leaves of Premna serratifolia L. (local name: arogo) is well known as food ingredient for fish/meat-based soup in Tentena, Indonesia. Evaluation of its bioactivities is needed. Objective: This study aimed to evaluate the α-glucosidase inhibitory and antioxidant activities of infusion and decoction of P. serratifolia leaves. Methods: The leaf samples were prepared by infusion and decoction and analysed for their α-glucosidase inhibitory and antioxidant activities, as well as total phenolic content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
2
9
0
2
Order By: Relevance
“…This study demonstrated that P. serratifolia leaves are inhibitors of α -glucosidase and α -amylase. This observation is in agreement with our previous study, in which it was shown that water extract inhibited α -glucosidase in a competitive mode [ 14 ]. On a previous report, the leaves of P. serratifolia have been reported to have hypoglycemic activity using animal model [ 37 ].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…This study demonstrated that P. serratifolia leaves are inhibitors of α -glucosidase and α -amylase. This observation is in agreement with our previous study, in which it was shown that water extract inhibited α -glucosidase in a competitive mode [ 14 ]. On a previous report, the leaves of P. serratifolia have been reported to have hypoglycemic activity using animal model [ 37 ].…”
Section: Resultssupporting
confidence: 94%
“…Stronger activity was observed for EEPS than WEPS ( p < 0.05). Scavenging activities found in these extracts are in agreement with previous studies [ 14 , 26 ]. Previously, extract of other part of P. serratifolia has been reported to have good activity on DPPH radicals.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…α-Glucosidase Assay α-Glucosidase inhibitory activities of fFJ of M.citrifolia was determined based on our reported procedure. 13 Different concentrations of fFJ were prepared by serial dilutions. The reaction mixture was prepared consisting of the sample (50 μl), 50 μl of phosphate buffer (50 mM, pH 6.8) and 50 μl of α-glucosidase (0.5 U/ml).…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…The inhibition mode of the most active extract was determined by performing an enzyme kinetic assay based on previous method. 22 In this assay, substrate (p-nitrophenyl α-D-glucopyranoside) was prepared at increasing concentrations (0.25 -1.25 mM). The solution was incubated with α-glucosidase (0.5 U/mL) in the absence and presence of extract (inhibitor) at different concentrations in phosphate buffer (50 mM pH 6.8).…”
Section: Determination Of α-Glucosidase Inhibition Modementioning
confidence: 99%